ANALISIS KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA - Nur Harini Khoiru Nisa (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
The purpose of this study was to determine the profile of students' mathematical reasoning abilities, profiles of visual, auditory, kinesthetic learning styles and the correlation of reasoning abilities with students' learning styles. This type of research is a non-experimental quantitative research using the correlation method. The technique used in obtaining the data for this study was a learning style questionnaire and a test of students' mathematical reasoning abilities. The research subjects were students of class VIII SMPIT Al-Falah Bandungan with a total of 89 students. The results of this study showed that the profile of students' mathematical reasoning abilities of class VIII SMPIT was in the medium category with a percentage of 50%. For the profile of the learning style of class VIII SMPIT students, the trend of learning style is visual learning style with a percentage of 40%, auditory learning style by 37%, and as many as 17% have a kinesthetic learning style, and there are 2 students who have a combined learning style, namely learning styles visual-kinesthetic and visual-auditorial. Then the relationship between mathematical reasoning ability and student learning style is in a strong interval with a value of 0.4536464 and a significant correlation level of 2.561 with a relationship level of 19%, it proves that 19% of students' mathematical reasoning ability is determined by learning style, and the rest is determined by factors other.